Festschrift 200 Jahre Juristische Fakultät der Humboldt-Universität zu Berlin: Geschichte, Gegenwart und Zukunft - Grundmann, Stefan (de Gruyter, 2010)
The law department was founded together with the University of Berlin in 1810 by King Friedrich Wilhelm III. Many well-known attorneys have taught at the University of Berlin: Friedrich Carl von Savigny in the early years, followed by distinguished persons such as Levin Goldtschmidt, Otto von Gierke, Josef Kohler, Rudolf Smend, Martin Wolff, Ernst Rabel and Friedrich von Liszt. The commemorative publication History and the Present is published in honor of the 200-year anniversary of the law department
Includes bibliographical references
Keywords: Humboldt-Universität zu Berlin / Juristische Fakultät; Universität / Juristische Fakultät; Humboldt-Universität zu Berlin -- Juristische Fakultät; Aufsatzsammlung